What Was the Name of That Drug? How Medical Students can Make the Most Out of Their Education - Riahi, Aryan; Jung, David (International Journal of Medical Students, 2019)
Consolidating all of the knowledge that medical students are expected to learn in their first two years of education can be challenging. Strategies for committing concepts to memory are explored. The importance of making the most out of case-based learning is emphasized. In contrast with passive-styled learning in lectures, CBL takes an active approach requiring students to apply critical thinking. The power of active recall in committing information to memory is also delved into. In particular, one effective and popular form of active recall known as the testing effect is highly recommended. Applying these strategies will help medical students develop a strong foundation for clerkship.